Experience of the Europol cooperation (Academic Journal of Internal Affairs, 2024)
Aim: The aim of the article is to present the practical experience of cooperation between Europol, which plays a key role in international criminal cooperation, and Hungary.Methodology: The author collected knowledge about the operation of Europol and its investigative support services by studying the available EU legislation, and by working as the Head of the Hungarian Liaison Bureau at Europol, as well as by carrying out the tasks of the former expert in the cyber-attacks priority and the deputy national EMPACT coordinator.Findings: Europol’s system of cooperation with the Member States and operational and strategic partners provides the law enforcement agencies of the countries concerned with an opportunity that no other agency, institution or organisation can offer. In addition to supporting specific investigations, the institutional system also provides countries with IT, strategic and financial support.Value: The article aims to provide a practical and comprehensive overview of the state of cooperation with Europol, to give a deeper insight into the day-to-day work of the law enforcement and judicial authorities and to provide the interested reader with contextualized insights into the steps and processes involved.
Keywords: Europol; EMPACT; SOCTA; SIRIUS